2009
DOI: 10.3982/ecta7417
|View full text |Cite
|
Sign up to set email alerts
|

Inference for Continuous Semimartingales Observed at High Frequency

Abstract: The econometric literature of high frequency data often relies on moment estimators which are derived from assuming local constancy of volatility and related quantities. We here study this local-constancy approximation as a general approach to estimation in such data. We show that the technique yields asymptotic properties (consistency, normality) that are correct subject to an ex post adjustment involving asymptotic likelihood ratios. These adjustments are given. Several examples of estimation are provided: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…2.1.5 for an intuitive exposition. Formal results why this works in specific settings rely on Girsanov's theorem, see, e.g., Gugushvili et al (2020), Hoffmann et al (2012, Mykland and Zhang (2009). Further reasons why one would like to set b = 0 are that b is a nuisance parameter, in specific applications its appropriate parametric form might be unknown, and finally, a single observed time series is not sufficient to learn b consistently (see Ignatieva & Platen 2012).…”
Section: Linear State Space Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1.5 for an intuitive exposition. Formal results why this works in specific settings rely on Girsanov's theorem, see, e.g., Gugushvili et al (2020), Hoffmann et al (2012, Mykland and Zhang (2009). Further reasons why one would like to set b = 0 are that b is a nuisance parameter, in specific applications its appropriate parametric form might be unknown, and finally, a single observed time series is not sufficient to learn b consistently (see Ignatieva & Platen 2012).…”
Section: Linear State Space Modelmentioning
confidence: 99%
“…There exists a large body of statistics and econometrics literature on nonparametric volatility estimation under microstructure noise. See, e.g., Hoffmann et al (2012), Jacod et al (2009), Mykland and Zhang (2009), Reiß (2011), Sabel et al (2015); a recent overview is Mykland and Zhang (2012). The literature predominantly deals with estimation of the integrated volatility t 0 s 2 (u)du, although inference on s has also been studied in several of these references.…”
Section: Introductionmentioning
confidence: 99%
“…(2005), Mykland and Zhang (2009), Aït-Sahalia et al (2010), Aït-Sahalia et al (2011), Zhang et al (2005), and Zhang (2006); the realized kernel suggested by Barndorff-Nielsen et al (2008) and Barndorff-Nielsen et al (2011); the quasi-maximum likelihood method studied by Xiu (2010); and the pre-averaging approach proposed by Jacod et al (2009) and Li (2013).…”
Section: Introduction 11 Motivationmentioning
confidence: 99%
“…Realized variance, the most commonly used realized measure, is constructed by summing up squared intra-daily returns. There is an extensive statistical theory for this subject derived in papers by Barndorff-Nielsen and Shephard (2002), Meddahi (2002), Andersen et al (2003), and Mykland and Zhang (2009), among others.…”
Section: Introductionmentioning
confidence: 99%